A comparison of turbulent transport in a quasi-helical and a quasi-axisymmetric stellarator. (October 2019) - McKinney, I. J.; Pueschel, M. J.; Faber, B. J.; Hegna, C. C.; Talmadge, J. N.; Anderson, D. T.; Mynick, H. E.; Xanthopoulos, P.
Abstract : Ion-temperature-gradient-driven (ITG) turbulence is compared for two quasi-symmetric (QS) stellarator configurations to determine the relationship between linear growth rates and nonlinear heat fluxes. We focus on the quasi-helically symmetric (QHS) stellarator HSX and the quasi-axisymmetric (QAS) stellarator NCSX. In normalized units, HSX exhibits higher growth rates than NCSX, while heat fluxes in gyro-Bohm units are lower in HSX. These results hold for simulations made with both adiabatic and kinetic electrons. The results show that HSX has a larger number of subdominant modes than NCSX and that eigenmodes are more spatially extended in HSX. We conclude that the consideration of nonlinear physics is necessary to accurately assess the heat flux due to ITG turbulence when comparing QS stellarator equilibria.